Visual debuggers and the deaf: paving the way to the workplace - Nascimento, Marcos Devaner do; Oliveira, Francisco Carlos de Mattos Brito; Freitas, Adriano Tavares de; Silva, Lidiane Castro (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2015: Anais do XXVI Simpósio Brasileiro de Informática na EducaçãoDO - 10.5753/cbie.sbie.2015.792, 2015)
It is not enough to offer accessible learning material, accessible learning platform and bilingual tutoring. Deaf or hearing impaired (DHI) java graduates still show poorer perfomance in debugging tasks when compared to their hearing counterparts. Direct manipulation and visual debuggers might improve the odds of securing the DHI a position in the IT industry. We present a study where DHI java graduates perform debugging tasks using a visual debugger and Eclipse. Situated analysis, usability assessment and a formal task performance evaluation show visual debuggers might benefit the DHI programmer.